Evaluation of Integrity Zones in Public Services at the Faculty of Law, Universitas Singaperbangsa Karawang - Kurnia, Asep Rahmat; Abdulloh; Sholeh, Slamet; Ruslan, Undang (Research Horizon, 2025)
The development of an integrity zone in higher education institutions is a national effort to create clean, accountable, and high-quality public services. This study evaluates the quality of public services at the Faculty of Law, Universitas Singaperbangsa Karawang, in the context of ongoing integrity zone implementation. A quantitative survey approach using the service quality model was employed a questionnaire covering five dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The research respondents consisted of three groups of service users, namely educational staff, lecturers, and students, who were selected using proportional random sampling techniques. Data were collected online and analyzed descriptively. The results show that service quality is in the good category with average scores of 2.64 (educational staff), 2.71 (lecturers), and 3.25 (students). Reliability and assurance received the highest ratings across all groups, while empathy (among staff) and tangibles (among students) scored the lowest. Students were the most satisfied group, whereas educational staff were the most critical. The study concludes that the integrity zone initiative has been moderately effective, but further improvement in interpersonal communication, response speed, and digital-physical facilities is still required to achieve excellent service standards.